TANGGUNG JAWAB PENYEDIA KONTEN TIKTOK ATAS PENGUNGGAHAN FILM BAJAKAN MELALUI APLIKASI TIKTOK (STUDI KASUS : PELANGGARAN PEMILIK HAK CIPTA SINEMATOGRAFI) - Chindy (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The purpose of this research is to examine the obligations of Tiktok content facilitators regarding uploading imitation films from the Tiktok platform and law enforcement efforts against cinematographic copyright errors related to uploading imitation films from the Tiktok platform by content owners. This article uses normative juridical legal research methods using statutory and conceptual approaches. The results of this research prove that TikTok content owners must be responsible for preventing counterfeit films by acting directly to block user accounts. However, law enforcement regarding cinematography copyright violations has not been effective because there are still many content creators who upload imitation films to the TikTok application.